Intrinsic moral hazard - Korkut A. Ertürk (The University of Utah, Department of Economics, 2019)
The paper argues that financial deregulation incentivized financial firms to take excessive risks and over-expand because it turned social insurance against systemic risk into a common pool (or open) resource. The increased size and complexity of deregulated financial markets in turn raised the social cost of imposing discipline in financial markets to prohibitive levels. Because this undermined the credibility of the regulators' threats of sanction, their deterrence strategy was from then on subgame imperfect. This suggests that moral hazard can be explained by the market expectation that regulators would act like a rational maximizer rather than by the things they irrationally did or not do.
Keywords: D72; C70; G20; G18; 330; systemic risk; moral hazard; financial deregulation; coordination failure; excessive risk taking and financial crisis